Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acs.jpcb.2c00778
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approach to Interaction Studies of Pyrene Derivatives with Bovine Serum Albumin: Insights from Theory and Experiment

Abstract: This work aimed to investigate the interaction of bovine serum albumin with newly synthesized potent new pyrene derivatives (PS1 and PS2), which might prove useful to have a better antibacterial character as found for similar compounds in the previous report [ Bioconjugate Chemistry 2014 12 2269 2284 ]. However, to date, binding studies with plasma protein are still unknown. Steady-state fluorescence spectroscopy and lifetime fluorescence studies show that t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…[3,4] Furthermore, incorporation of heterocyclic rings in the structural framework of chalcones will further increase their bioactivity. C-glycoside incorporated with chalcone which is said to be sugar chalcone hybrids [5] are expected to have wide applications in the field of medicine as drug. [6] Serum Albumins are one of the most abundant and soluble protein in blood plasma.…”
Section: Introductionmentioning
confidence: 99%
“…[3,4] Furthermore, incorporation of heterocyclic rings in the structural framework of chalcones will further increase their bioactivity. C-glycoside incorporated with chalcone which is said to be sugar chalcone hybrids [5] are expected to have wide applications in the field of medicine as drug. [6] Serum Albumins are one of the most abundant and soluble protein in blood plasma.…”
Section: Introductionmentioning
confidence: 99%
“…26 Cathepsin B inhibitors are of considerable contemporary therapeutic significance. Pyrene based Schiff base ligands are well known for their antimicrobial, 27 chemosensing 28 and protein binding 29 aspects. However, pyrene based Schiff base ligands have not been employed previously as inhibitors of digestive enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35] Interaction of different substrates with pyrene is also undertaken in several other studies highlighting the functionalization of pyrene or other pyrene-like model systems for a range of applications. [25][26][27]36,37 Recently, the interaction of pyrene with biomolecules and other systems have also been studied. Sengottiyan et al has reported the binding studies of plasma proteins pyrene derivatives addressing the antimicrobial resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Sengottiyan et al has reported the binding studies of plasma proteins pyrene derivatives addressing the antimicrobial resistance. 36 Another study reports the role of pyrene in probing different protein conformations thereby highlighting its importance in molecular organization of biological molecules 37 and in elucidating how mechanochromic luminescence behaviours can be modulated by side-chain substituents. 38 Several studies have reported pyrene as a model system for studying the properties of graphene for various applications, viz., eld effect transistors, hydrogen chemisorption, reactions in interstellar medium, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation